H.A.R. Tilaar Multicultural Education in Inclusive Indonesian Learning: Pendidikan Multikultural H.A.R. Tilaar dalam Pembelajaran Inklusif Indonesia - Anggita, Lonie; habibullah, Jumadil Awali; Nurlaili, Nurlaili (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Indonesia is characterized by cultural, ethnic, religious, and social diversity that requires educational strategies capable of fostering tolerance and national cohesion. In this context, multicultural education becomes an essential approach for cultivating inclusive values within the educational system. Specific Background: H.A.R. Tilaar is recognized as a prominent Indonesian thinker who conceptualized multicultural education as a philosophical and pedagogical foundation for managing diversity in education. His perspective emphasizes education as a process of humanization and liberation while promoting democratic and inclusive learning environments. Knowledge Gap: Although Tilaar’s ideas are widely discussed in educational discourse, comprehensive studies connecting his philosophical concepts with concrete learning practices in Indonesian classrooms remain limited. Aims: This study aims to analyze Tilaar’s concept of multicultural education and examine its application in the learning process. Results: Using a qualitative library research approach with descriptive analysis, the findings show that Tilaar’s multicultural education promotes dialogical pedagogy, contextual learning, and the role of teachers as transformative agents. Its application in classroom practice includes integrating local cultural values, developing inclusive learning materials, creating democratic classroom interactions, and implementing authentic assessment that considers attitudes such as empathy and tolerance. Novelty: The study provides a comprehensive perspective by integrating Tilaar’s philosophical ideas with practical strategies for implementing multicultural education in learning processes. Implications: These findings demonstrate that Tilaar’s thought offers both philosophical and practical foundations for implementing multicultural education that supports inclusive nationalism and strengthens Indonesia’s cultural resilience within a pluralistic society. Highlights • Tilaar’s perspective frames multicultural education as a process of humanization and liberation in schooling.• Dialogical pedagogy and integration of local cultural values shape democratic classroom practices.• Inclusive learning materials and authentic assessment support tolerance and cultural awareness among students. Keywords Multicultural Education; H.A.R. Tilaar; Inclusive Learning; Dialogical Pedagogy; Cultural Diversity